Implementasi Hukum Pasar Modal terhadap Praktik Perusahaan Sekuritas di Indonesia Pasca Covid-19 - Edina, Sheilla Ariestia; Sudarto, Sudarto (FOCUS, 2025)
The COVID-19 pandemic had a significant impact on Indonesia's capital market, including securities companies that act as intermediaries in securities transactions. Economic instability and high market volatility created legal challenges in regulatory compliance, policy adaptation, and investor protection. This study aims to analyze the implementation of capital market law on the practices of securities companies post-COVID-19, with a case study on PT. OSO Sekuritas Indonesia. The research employs a normative juridical approach supported by empirical data, including interviews with industry stakeholders and an analysis of policies issued by the Financial Services Authority (OJK) and the Indonesia Stock Exchange (BEI). The findings reveal that the pandemic accelerated digital transformation in the capital market sector, increased regulatory complexity, and strengthened OJK’s role in enforcing legal compliance among securities companies. However, major challenges include regulatory uncertainty, default risks, and stricter supervision. The long-term legal implications of the pandemic highlight the need for capital market policy revisions to be more adaptive to crises, enhanced investor protection, and stronger regulations on digital technology use in securities activities. This study is expected to contribute to the development of Indonesia’s capital market law, particularly in formulating policies that are more responsive to market dynamics and the needs of securities companies and investors.